"We have to focus on improving our and our next generation's rights!" Exploring critical literacy in a third space for Korean female high school students. Issue 2 (3rd April 2021) - Cho, Hyesun; Johnson, Peter
ABSTRACT: This study provides a situated account of a native English-speaking teacher who implements critical literacy in the English as a foreign language (EFL) classroom at a Korean high school. Teacher interview data and student presentations are analyzed to depict how a third space created by the EFL teacher and his students allowed meaningful and relevant critical literacy activities for the female high school students. Mutual trust between the teacher and students as well as support from co-teachers and school administration emerge as central themes in the third space in which students conduct research on and present social topics, such as gender equality in Korea and beyond. Findings reveal that EFL learners are capable of enacting critical literacy despite the assumptions about the instructional challenges due to their linguistic and cultural backgrounds if they are given opportunities for critical conversations about controversial topics.